LYKKELIGST AT HVILE PÅ... - Knudsen, Anne (Tidsskriftet Antropologi, 1999)
This article assesses the perennial and perhaps unquenchable thirst for the anecdotal in anthropological research and reflection. Our informants, who may not give us long interviews or life histories, tell us, nevertheless, rich anecdotes in everyday conversations. Their choices of anecdotes become our key indices. Ruth Benedict and E.E. Evans-Pritchard are the article’s chief cases. The social function of memory is significant, and the article urges paying attention to etymologies, especially of the word “anecdote”, which literally means “unpublished” and alludes to the secretive that cannot be kept secret. The anecdote becomes public but maintains its intimacy. Both the telling and the told enter into the pictorial, illustrative summation. The iconographic method of art and literary historians is akin to ethnographic method. By recognizing and cultivating this kinship, we become betler craftsmen in anthropology. Vividness is inherent in theory.